Combined quantification of paclitaxel, docetaxel and ritonavir in human feces and urine using LC‐MS/MS. (29th August 2013) - Hendrikx, Jeroen J. M. A.; Rosing, Hilde; Schinkel, Alfred H.; Schellens, Jan H. M.; Beijnen, Jos H.
ABSTRACT A combined assay for the determination of paclitaxel, docetaxel and ritonavir in human feces and urine is described. The drugs were extracted from 200 μL urine or 50 mg feces followed by high‐performance liquid chromatography analysis coupled with positive ionization electrospray tandem mass spectrometry. The validation program included calibration model, accuracy and precision, carry‐over, dilution test, specificity and selectivity, matrix effect, recovery and stability. Acceptance criteria were according to US Food and Drug Administration guidelines on bioanalytical method validation. The validated range was 0.5–500 ng/mL for paclitaxel and docetaxel, 2–2000 ng/mL for ritonavir in urine, 2–2000 ng/mg for paclitaxel and docetaxel, and 8–8000 ng/mg for ritonavir in feces. Inter‐assay accuracy and precision were tested for all analytes at four concentration levels and were within 8.5% and <10.2%, respectively, in both matrices. Recovery at three concentration levels was between 77 and 94% in feces samples and between 69 and 85% in urine samples. Method development, including feces homogenization and spiking blank urine samples, are discussed. We demonstrated that each of the applied drugs could be quantified successfully in urine and feces using the described assay. The method was successfully applied for quantification of the analytes in feces and urine samples of patients. Copyright © 2013 John Wiley & Sons, Ltd.